Is Superdiversity a Useful Concept in European Medical Sociology? - Bradby, Hannah; Green, Gill; Davison, Charlie; Krause, Kristine (Frontiers in Sociology, 2017)
Medical sociology has a poor track record of researching diversity in theoretically innovative ways. This paper notes usage of the term superdiversity in migration and urban studies, to ask about its utility in general and more specifically for researching the social production of health and illness. Referring to a multi-country interview study about healthcare seeking strategies, the need to understand the diversification of diversity and the challenges for multi-method health research are described. Six interviews each were conducted in Germany, Spain, Sweden and the UK, to give a diversity sample of 24 adults who described their strategies and practice when seeking healthcare. In discussing how far superdiversity can help to model socio-economic and cultural changes already identified as challenging health policy and service provision, the paper draws on case study material. The complex intersecting dimensions of population diversity to which superdiversity draws attention are undoubtedly relevant for commissioning and improving healthcare and research as well as policy. Whether models that reflect the complexity indicated by qualitative research can be envisaged in a timely fashion for quantitative research and questions of policy, commissioning and research re key questions for the superdiversity’s ongoing usefulness as a concept.